Gender and poverty : microfinance for rural women in Yilong County, Sichuan Province of China - Guo, Ruixiang; Kelkar, Govind; Dale, Reidar; Walter, Pierre G. (Bangkok : Asian Institute of Technology, 1997)
The microfinance component of the UNDP Project in Yilong County, Sichuan Province of China is an example of a group based lending approach with the purpose of seeking a sustainable credit and saving model for the poor, particularly poor women. The project contributes to the Chinese Government's 8-7 poverty alleviation programme for eliminating abject poverty by the year 2000, focused on households. As elsewhere, the burden of poverty falls heaviest on women. Much of the gender disparity in deprivation stem from inequality in the allocation of resources within households. This study examines the gender issues in alleviation of poverty through the extension of microfinance, with its main focus on the UNDP-Yilong model. A detailed gender focused situation analysis of the study area, women and microfinance in Yilong project, its current achievements and limitations and discussions and recommendations for sustainable development of the Yilong model and empowerment of women through the utilization of microfinance based on the primary and secondary data captured for this study were done in the thesis. This Yilong model for microfinance is still very new. The results of this study were that there have been some early successes from implementation of the microfinance activities in Yilong. These include creating field staff who are able to form poor women's groups and centers, lending to the targeted poorest households, particularly women, reaching the 100% repayment rate, collecting the required savings and organizing some technical assistance for beneficiaries. Furthermore, the findings from this study was that small loans do strengthen rural women's economic role. By strengthening their economic roles, and increasing their ability to contribute to their family's support, microfinance empowers women to a certain extent in capability building, active participation in decision-making within the household and outside in the community, participation in public affairs and involvement in the local market. Gender relations within the household and in the community are changing. Microfinance as a means for reaching the goal of empowerment of the poor, particularly poor women, provides a beginning and helps the disadvantaged to transform their subordinate position. However, only giving poor women access to loans is not enough. Much more important is their control over this important productive resource. Loans under women's names do not mean that they are managed and all decisions for their utilization made by women. An extensive impact analysis on women's attitudes and behaviors, employment patterns and changes in the gender relations within households and in the community remains to be done. ii The Yilong model does face problems in the expansion of microfinance activities due to a need for adequately qualified CCCs and GOs, self-sufficient institutions and weakness in the technical support for the poorest households. Strengthening the structure of YRDA, and reinforcing coordination and consolidation of the Yilong model are the major focus points for the sustainable development of the Yilong model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science. School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Women in development -- China -- Sichuan; Poverty -- China -- Sichuan